Fumarate hydratase-deficient renal cell carcinoma: a case report and review of the literature - Yanting Lv; Lide Song; Mengjun Hu (Journal of Medical Case Reports, 2023)
Abstract Background Fumarate hydratase-deficient renal cell carcinoma is a rare pathological subtype that was defined by the World Health Organization (WHO 5th edition) in 2022. At present, only a few hundreds of cases have been reported worldwide, mainly in Europe and the United States. A case of a Chinese patient is reported here, along with a literature review. Case report A 60-year-old Asian male who complained of hematuria for 20 days was admitted to the hospital. Contrast enhanced Computer Tomography showed that the volume of the right kidney was increased, with a patchy low-density shadow with infiltrative growth inside that had a significantly lower signal intensity than the renal cortex; thus, the possibility of collecting duct carcinoma or lymphoma, was considered. Enlarged perirenal and retroperitoneal lymph nodes were also seen, along with bilateral renal cysts. Eight years prior, ultrasonography had shown a complex renal cyst in the right kidney, and no treatment was administered at that time. Laparoscopic radical nephrectomy of the right kidney was performed this time, and the postoperative specimens were submitted for pathological examination. Because immunohistochemistry showed the loss of fumarate hydratase protein expression and the possibility of fumarate hydratase-deficient renal cell carcinoma was considered, corresponding molecular pathological tests were performed, and the results showed an FHp.R233H (arginine > histidine) germline mutation (inactivation mutation). The postoperative pathological diagnosis was fumarate hydratase-deficient renal cell carcinoma in the right kidney, T3aN1M0. The patient was treated with sunitinib, and bone and liver metastases developed half a year later. The treatment was then changed to axitinib and toripalimab. At present, the patient is in stable condition, and there has been no progression of the metastases. Conclusion Fumarate hydratase-deficient renal cell carcinoma is a very rare renal tumor that is defined on a molecular basis. It is highly malignant and metastasizes early. Therefore, fully understanding the disease, enabling detection and diagnosis and administering treatment are particularly important.